Gall-Inducing Tephritid Flies (Diptera: Tephritidae): Evolution and Host–Plant Relations - Korneyev, Valery A. (Frontiers in Ecology and Evolution, 2021)
The molecular-based phylogenetic analysis of the subfamily Tephritinae, the subfamily that contains almost all the cecidogenous species of the family Tephritidae, has reassigned several tribes and groups of genera and modified their concepts based on morphology alone to other tribes and, thus, changed the hypothetical scenarios of evolution of fly/host–plant relations and, in particular, the gall induction in different phylogenetic lineages. Gall induction is shown to arise independently within the Myopitini (in two lineages), Cecidocharini, Tomoplagia group of genera, Eurostini, Eutreta, Tephritis group of genera, Platensinini, Campiglossa group of genera, and Sphenella group of genera independently and more or less synchronously due to the shift to host plants with smaller flower heads and sensitive to larval feeding causing tissue proliferation. This was possibly a result of temporary aridization of the grassy biomes in the Nearctic and Afrotropic regions in the late Miocene or early Pliocene.